Harnessing the tenets of health promotion and wise reasoning in managing the COVID-19 pandemic in Ghana and similar contexts - Kutor, S.K.; Ablo, A.D.; Annan-Aggrey, E.; et al. (African Geographical Review, 2022)
The emergence of COVID-19 in December 2019 produced new geographic spaces characterized by physical and social distancing with concomitant surprises. In Ghana, management of the first and second waves of the pandemic garnered mixed reactions from the populace. Against these perspectives, this commentary explored the critical role of health promotion and wise reasoning tenets in dealing with the COVID-19 pandemic in Ghana, specifically through the following eight principles: intellectual humility; acknowledging uncertainty and change; perspective-taking of different viewpoints; integration of diverse perspectives; intersectorality; sustainability; empowerment and public health engagement; and equity. Our analyses demonstrate that wise reasoning and health promotion from Ghana’s political authorities are critical to ensuring citizens’ compliance with the several measures that require a change of behavior.
Research Article
Keywords: COVID-19; wise reasoning; health promotion